2006
DOI: 10.1159/000096681
|View full text |Cite
|
Sign up to set email alerts
|

Agitation in Dutch Institutionalized Patients with Dementia: Factor Analysis of the Dutch Version of the Cohen-Mansfield Agitation Inventory

Abstract: Background/Aims: To establish the construct validity of the Dutch version of the Cohen-Mansfield Agitation Inventory (CMAI-D) in institutionalized patients with dementia. Methods: The CMAI-D was administered to a large sample of 1,437 patients with moderate to severe dementia, receiving nursing home or outreaching nursing home care. Exploratory factor analysis was used to examine the behavioral dimensions underlying CMAI-D observations. Results: A restricted 3-factor solution showed 3 factors, i.e. physical ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 87 publications
3
65
1
5
Order By: Relevance
“…Nonetheless, 3 out of the 9 items of the Norwegian version of the BARS represent verbal expressions (repetitive sentences and questions, making strange noises and complaining). Screaming did not contribute essentially to the factors of the CMAI found in various studies using a factor analysis of the CMAI [7,21,22,24,35] . Additionally, Rabinowitz et al [7] reports that in 6 studies performing a factor analysis on the CMAI only 3 showed a loading of 'screaming' as 6 0.40.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Nonetheless, 3 out of the 9 items of the Norwegian version of the BARS represent verbal expressions (repetitive sentences and questions, making strange noises and complaining). Screaming did not contribute essentially to the factors of the CMAI found in various studies using a factor analysis of the CMAI [7,21,22,24,35] . Additionally, Rabinowitz et al [7] reports that in 6 studies performing a factor analysis on the CMAI only 3 showed a loading of 'screaming' as 6 0.40.…”
Section: Discussionmentioning
confidence: 58%
“…Some studies, performing a factor analysis of the CMAI, included just patients with moderate to severe dementia [21] or subjects with dementia exhibiting behavioral problems [22] . A further limitation of our study is that we report results from Norwegian nursing home patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we used factor scores of the CMAI instead of the total score to provide clarity regarding the possible differences in specific aspects of aggression and thereby prevent a loss of information. However, the factor structure of both the NPI-NH and CMAI was evaluated in older NH residents with dementia and has not yet been established in YOD (Zuidema et al, 2007a(Zuidema et al, , 2007b. Furthermore, part of the YOD group was drawn from an older cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The total CMAI score ranges from 29 to 203. We used CMAI factors based on a previous study in which three CMAI factors in a large NH sample were found: physically non-aggressive behaviors (range 7-49), physically aggressive behaviors (range 8-56), and verbally agitated behaviors (range 4-28) (Zuidema, de Jonghe, Verhey, & Koopmans, 2007b).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…4,15 All types of agitation increase as dementia progresses and often persist. 20,49 Agitation and aggression are often the reason for use of psychotropic agents and for referral to specialist services. Cohen-Mansfield et al 42 propose that verbally agitated behaviours may be a form of help-seeking behaviour for residents with physical disease and depressed affect.…”
Section: Agitation-aggressionmentioning
confidence: 99%